EFFECTS OF HIGH INTENSITY AEROBIC INTERVAL TRAINING AND REPEATED SPRINT TRAINING ON AEROBIC AND ANAEROBIC PERFORMANCE IN FOOTBALL PLAYERS - Ates, Osman (Acta Scientiae et Intellectus, 2024)
The aim of this study is to examine the effects of the high-intensity aerobic interval and the repeated sprint training model on YYIRT1, RAST and agility. 20 young players (mean age: 17.4, ± age: 0.64 years, mean body weight: 64.7 kg± body weight: 6.04 kg, mean height: 172.6 cm, ± height: 4.57cm) participated. After the players completed YYIRT1, RAST and agility pretests, they were separated into 2 groups. Players in the first group completed 3x (6x40m) repeated sprint training twice a week for six weeks while players in the second group completed 4x4 minute running at 90% maximum heart rate for high-intensity aerobic interval training twice a week for six weeks. Although repeated sprint and high-intensity aerobic interval training had positive effects on YYIRT1, no statistically significant difference was found between the groups (p>0.05). However, significant differences were found in RAST test total time (TT) and the fatigue index (FI) of the players in the repeated sprint group (p<0.05). Repeated sprint or high-intensity aerobic interval training practiced twice a week were observed to affect YYIRT1 levels positively. In the literature, although significant differences in YYIRT1 results were indicated applying the repeated sprint training model, a significant difference was not seen in the current study. However, within the group using the repeated sprint training model, repeated sprint total time decreased and fatigue index improved, showing an improvement in their performance.